Exploring the Interventional Effect of Languaging Activities on L2 Motivation Among Chinese EFL Learners - Chili Li; Xuemei Jiang (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
Motivational languaging activities (MLAs) encourage learners to externalize their self-perceptions through oral or written forms and promote learners’ cognitive development. However, limited research has investigated the impact of MLAs on learners’ L2 motivation. To bridge this gap, the present study sought to unveil the effect of MLAs on Chinese tertiary English as a foreign language (EFL) learners’ motivation. Participants were 156 Chinese tertiary EFL learners divided into four groups: Experimental Group 1 (EG1), EG2, EG3, and a Control Group (CG). The experimental groups performed the MLAs in spoken, written, and spoken plus written forms respectively, while the CG received no MLA intervention. Motivational dynamics were measured with an adapted questionnaire administered at the beginning and end of the intervention, and qualitative data were collected through group discussions and opinion writing. The results revealed various degrees of enhancement in L2 motivation across the three experimental groups, highlighting the effectiveness of spoken MLAs in significantly increasing the Ought-to L2 Self among the participants.